2009
DOI: 10.1002/zoos.200800021
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution and genital morphology of the genera Lozekia Hudec, 1970 and Kovacsia Nordsieck, 1993 (Mollusca, Gastropoda, Hygromiidae)

Abstract: Key Wordstranssilvanica transsylvanica deubeli kovacsi zoogeography Pannonicum Carpathicum dart-sac complex spermatophore AbstractThe Lozekia-Kovacsia species group comprises three species occurring in the Carpathian-Pannonian region, namely Lozekia transsilvanica (Westerlund, 1876), Lozekia deubeli (M. Kimakowicz, 1890) and Kovacsia kovacsi (Varga & L. Pintr, 1972). These species are known to be distinguishable by their genital morphology but, up to now, only a few populations have been examined anatomically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…In our opinion, however, two of these arguments can not be substantiated. First, a recent study has shown that the penial papilla of K. kovacsi is longer, but does not differ structurally from those of the other two species (Fehér et al. 2009).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our opinion, however, two of these arguments can not be substantiated. First, a recent study has shown that the penial papilla of K. kovacsi is longer, but does not differ structurally from those of the other two species (Fehér et al. 2009).…”
Section: Discussionmentioning
confidence: 96%
“…This species group – i.e. the ‘ Lozekia– Gruppe’ in the sense of Nordsieck (1993) or the Lozekia–Kovacsia species group in the sense of Fehér et al. (2009)– comprises three conchologically similar, but anatomically well distinguishable species, belonging to two genera, viz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A biometriát mindenekelőtt a fossziliák osztályozásánál használják, tekintettel arra, hogy lágy rész hiányában a genitáliák vizsgálatára, kemo-és molekuláris taxonómia módszerek alkalmazására nem mindig van lehetőség (Szöőr et al 1992, Fehér et al 2009). Természetesen, megfelelő feltételek esetén a biometria alkalmazható recens fajok, alfajok, formák, variánsok vizsgálatára, megkülönböztetésére is (Lupu 1966, Petro 1963, Domokos 1980, 1984, Shikov & Zatravkin 1991.…”
Section: Bevezetésunclassified
“…In some cases the genital features are more important than the shell characters. In several taxa, shells are insufficient for identifcation (HAUSDORF 2000, 2003, FEHÉR et al 2009). Exact measurements and proportions of the genitalia are widely used in the family (e.g.…”
Section: Introductionmentioning
confidence: 99%